2017
DOI: 10.3390/w9010025
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Winter Baseflow in Response to Permafrost Thaw and Precipitation Regime Shifts in Northeastern China

Abstract: Abstract:Rapid permafrost thaw and precipitation regime shifts are altering surface and subsurface hydrological processes in arctic and subarctic watersheds. Long-term data (40 years) from two large permafrost watersheds in northeastern China, the Tahe River and Duobukuer River watersheds, indicate that winter baseflows are characterized by significant positive trends of 1.7% and 2.5%·year −1 , respectively. Winter baseflows exhibited statistically significant positive correlations with mean annual air tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 66 publications
(85 reference statements)
2
35
0
Order By: Relevance
“…Increase in winter baseflows in the Tahe River and Duobukuer River watersheds of north-eastern China may be due to enhanced groundwater storage and winter groundwater discharge caused by permafrost thaw. It could also be due to an increase in the wet season rainfall [34].…”
Section: Discussionmentioning
confidence: 99%
“…Increase in winter baseflows in the Tahe River and Duobukuer River watersheds of north-eastern China may be due to enhanced groundwater storage and winter groundwater discharge caused by permafrost thaw. It could also be due to an increase in the wet season rainfall [34].…”
Section: Discussionmentioning
confidence: 99%
“…So, winter baseflow at two watersheds in permafrost area of northeast China had a distinct annual increasing trend, 1–2%, and lagged MAT increase by only two years (Duan et al. ). However, the area where these processes are happening is relatively small and does not change our “present‐day” results significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Walvoord and Striegl 2007, Déry et al 2009, St Jacques and Sauchyn 2009, Sjöberg et al 2013, Connon et al 2014. Although various explanations for these trends have been proposed, several studies have shown that increases mainly occur when stream discharge is primarily groundwater-derived, suggesting that the changes are related to permafrost thaw (Walvoord and Striegl 2007, St Jacques and Sauchyn 2009, Duan et al 2017. Increased baseflow due to groundwater discharge may be caused by (1) increased hydrogeologic connectivity due to new groundwater pathways formed by permafrost thaw (Walvoord and Striegl 2007, St Jacques and Sauchyn 2009), (2) a local increase of precipitation and atmospheric moisture that enhances groundwater recharge (Connon et al 2014, Duan et al 2017, and/or (3) a temporary decrease in water storage capacity due to changes in land-surface cover (Connon et al 2014).…”
Section: Introductionmentioning
confidence: 99%